2017
DOI: 10.3390/molecules22050744
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin from Polygonum capitatum Protects against Gastric Inflammation and Apoptosis Associated with Helicobacter pylori Infection by Affecting the Levels of p38MAPK, BCL-2 and BAX

Abstract: Helicobacter pylori-associated gastritis is a major threat to public health and Polygonum capitatum (PC) may have beneficial effects on the disease. However, the molecular mechanism remains unknown. Quercetin was isolated from PC and found to be a main bioactive compound. The effects of quercetin on human gastric cancer cells GES-1 were determined by xCELLigence. H. pylori-infected mouse models were established. All mice were divided into three groups: control (CG, healthy mice), model (MG, H. pylori infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Quercetin inhibited vacuolation and caspase-3 activation in HeLa cells induced by the vacuolating cytotoxin A, protecting from gastric inflammation and apoptosis associated with H . pylori infection 57,58 . Kaempferol decreased transcription of type IV secretion system (T4SS) components involved in CagA injection and secretion system subunit protein A (SecA) of type V secretion system (T5SS) involved in VacA secretion, thereby producing an anti-inflammatory effect by suppressing the translocation of CagA and VacA proteins 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin inhibited vacuolation and caspase-3 activation in HeLa cells induced by the vacuolating cytotoxin A, protecting from gastric inflammation and apoptosis associated with H . pylori infection 57,58 . Kaempferol decreased transcription of type IV secretion system (T4SS) components involved in CagA injection and secretion system subunit protein A (SecA) of type V secretion system (T5SS) involved in VacA secretion, thereby producing an anti-inflammatory effect by suppressing the translocation of CagA and VacA proteins 59 .…”
Section: Discussionmentioning
confidence: 99%
“…It might be that cortactin plays a role during endosomal trafficking of VacA from the cell membrane to the mitochondria [104], but further investigations are clearly required to unravel the detailed function of cortactin in programmed cell death. In this regard, it is interesting to note that the bioactive compound quercetin from the plant Polygonum capitatum was shown to protect against gastric inflammation and apoptosis associated with H. pylori infection in mice by affecting the expression level of p38 MAP kinase, Bcl-2 and Bax [105]. Thus, quercetin can regulate the balance between gastric cell proliferation and apoptosis in the gastric epithelium and could be a novel candidate therapeutic agent to treat H. pylori-induced gastritis and other diseases.…”
Section: Role Of Cortactin In Vaca-induced Apoptosismentioning
confidence: 99%
“…A recent research found that quercetin has the anti-allergic properties characterized by stimulation of immune system, inhibition of histamine release, decrease in proinflammatory cytokines, and improvement in the Th1/Th2 balance ( 53 ). The experiment by Zhang et al showed that quercetin protected against gastric inflammation and apoptosis associated with HPI by affecting the levels of p38MAPK, BCL-2, and BAX ( 54 ). Thus, quercetin could act as an effective ingredient to protect against HPI and activate some pathways.…”
Section: Discussionmentioning
confidence: 99%